(3eUMa TQjas ((3eMQhSI GeO s)
(3ChdgG (B:s
(3ShQI GdaGJMI Ke GdHbQI s
(3BNQgG (B:s
(3ShQI GdfGS QHfG JbHd efG Efc CfJ GdSejY GdYdje GdYdje hGfaYfG HGdbQBf GdcQje Cejf hGdMeO ddg hMOg s
(3gPg GdeUMa GdTQja ecJhH Ydi QSe GdeUMa GdCeGe YKeGf Hf YaGf QVi Gddg Yfg heVHhW heUMM Ydi bQGFJjf MaU hCHi HcQ hQhGjI YGUes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B/ (3GdehUd (B(22) s
Keywords: (3GdcJH GdSeGhjIs